Moderation of Organizational Justice on the Influence of Leader-Member Exchange and Discipline on the Performance of ASN Employee - Lukiyana, Lukiyana; Wansesa, Fitri Nurjati (Almana : Jurnal Manajemen dan Bisnis, 2024)
Moderation of organizational fairness and leader-member exchange are important variables that can influence employee performance. This research aims to test and analyze the moderation of organizational justice on the influence of member-leader exchange on the performance of ASN employees of the Ministry of Maritime Affairs and Fisheries. population in this study used a sample of 82 respondents who were employees of the Ministry of Maritime Affairs and Fisheries. The data collection technique uses simple random sampling by distributing research questionnaires in the form of Google Forms via social media. The data processing method in this study is to use smartPLS version 4 to test the hypothesis. The results of this study indicate that leader-member exchange is proven to have a positive and significant effect on employee performance, discipline performance is proven to have a positive and significant effect on employee performance, and organizational justice is proven to affect employee performance. Moderation of Organizational Justice weakens but is significant for the effect of leader-member exchange on performance. Organizational justice strengthens and can moderate Discipline performance on employee performance.